2012
DOI: 10.3109/15513815.2012.659393
|View full text |Cite
|
Sign up to set email alerts
|

A Classic Twin Study of Isolated Gastroschisis

Abstract: The etiology of gastroschisis remains elusive. A classic twin study was used to assess the relative contribution of environmental and genetic factors in its development. Screening of 4872 twin pregnancies identified three unreported twin pairs comprising two monozygous and one dizygous discordant pair of twins. Review of the literature identified an additional 21 twin pairs. We observed lower pair- and proband-wise concordance rates for monozygotic compared to dizygotic twin pairs, pair- and proband-wise conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…20 1 Spina bifida Q05.9 1 Congenital malformaƟons of lung Q33.9 1 Other encephaliƟs, myeliƟs och encephalomyeliƟs G04. 8 1 Acute pericardiƟs I30.9 1 AccidenƟal suffocaƟon and strangulaƟon in bed W75 1 Intrauterine hypoxia P20. 9 1…”
Section: Discussionmentioning
confidence: 99%
“…20 1 Spina bifida Q05.9 1 Congenital malformaƟons of lung Q33.9 1 Other encephaliƟs, myeliƟs och encephalomyeliƟs G04. 8 1 Acute pericardiƟs I30.9 1 AccidenƟal suffocaƟon and strangulaƟon in bed W75 1 Intrauterine hypoxia P20. 9 1…”
Section: Discussionmentioning
confidence: 99%
“…In a twin study, Schultz et al [2012] found that the concordance rate was not significantly different amongst dizygotic twins (4 out of 8 twins) compared to monozygotic twins (2 out of 5 twins reported). If we include our case with concordant gastroschisis, 3 out of 6 monozygotic twins are concordant, which is equal the concordance observed in dizygotic twins.…”
Section: Discussionmentioning
confidence: 88%
“…The classic monozygotic (MZ)-dizygotic (DZ) twin comparison is an informative tool for investigating genetic and environmental influences on human health and behavior. Greater resemblance within MZ compared with DZ twin pairs is consistent with genetic components to the condition under study [1]. Studying MZ twins reared apart from birth (MZA) is an especially powerful variant of the classic twin design.…”
Section: Introductionmentioning
confidence: 94%
“…Identical twins doubly exchanged at birth: a case report of genetic and environmental influences on the adult epigenome Epigenomics (2017) 9 (1) future science group Case Report Segal, Montoya, Loke & Craig that epigenetic drift may be driven by discordance in the rearing environments of MZT pairs [12]. However, MZT and MZA pairs show comparable phenotypic similarity across a range of measures, including EEG, height, heart rate, blood pressure, electrodermal response, personality and well-being [13].…”
Section: Introductionmentioning
confidence: 99%